Beginning Java EE 6 Platform with GlassFish 3 2nd Edition - Goncalves, Antonio (Apress, 2012)
In today’s business world, applications need to access data, apply business logic, add presentation layers, and communicate with external systems. That’s what companies are trying to achieve while minimizing costs, using standard and robust technologies that can handle heavy loads. If that’s your case, you have the right book in your hands. Java Enterprise Edition appeared at the end of the 1990s and brought to the Java language a robust software platform for enterprise development. Challenged at each new version, badly understood or misused, overengineered, and competing with open source frameworks, J2EE was seen as a heavyweight technology. Java EE benefited from these criticisms to improve and is today focused on simplicity. If you are part of the group of people who still think that “EJBs are bad, EJBs are evil,” read this book, and you’ll change your mind. EJBs (Enterprise Java Beans) are great, as is the entire Java EE 6 technology stack. If, on the contrary, you are a Java EE adopter, you will see in this book how the platform has found equilibrium, through its ease of development in all the stacks, new specifications, lighter EJB component model, profiles, and pruning. If you are a beginner in Java EE, this is also the right book: it covers the most important specifications in a very understandable manner and is illustrated with a lot of code and diagrams to make it easier to follow.